ANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP PERUBAHAN LABA PADA EMITEN SYARIAH YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Purnama, Yuli Mulia; Muzahid, Mukhlisul; Safaruddin, Safaruddin (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: Analysis of the Effect of Profitability, Liquidity and Solvency on Profit Changes in Sharia Issuers Listed in the Jakarta Islamic Index for the 2018-2020 Period.  This study aims to test and analyze whether Return On Equity (ROE), Current Ratio (CR) and Debt to Equity Ratio (DER) have a significant effect on earnings changes.  This study uses a quantitative descriptive approach, the type of data used is panel data, with panel data regression analysis method using Eviews 9 as a data processing tool.  Total population of 45 companies, research samples using purposive sampling obtained as many as 18 samples.  Before being analyzed, the data used were first tested for classical assumptions which include (normality test, multicollinearity test and heteroscedasticity test), panel data regression test and hypothesis testing using simultaneous test and partial test in the table with a significant value of 0.05.  The results showed that simultaneously Return On Equity (ROE), Current Ratio (CR) and Debt to Equity Ratio (DER) had a significant effect on earnings changes.  Partially Return On Equity (ROE) and Current Ratio (CR) have a positive and significant effect on changes in earnings, while the Debt to Equity Ratio (DER) has no significant effect on changes in earnings.  The results of the Adjusted R Square test show that the variation in the dependent variable of earnings changes that can be explained by Return On Equity (ROE), Current Ratio (CR) and Debt to Equity Ratio (DER) is 40% while the remaining 60% can be explained by other variables outside  this research..Keywords: Return On Equity, Current Ratio, Debt to Equity Ratio and Profit Changes